ЦИЛИНДРИЧЕСКИЕ ГАРМОНИКИ МАГНИТНОГО ПОЛЯ ПРОДОЛЬНО НАМАГНИЧЕННОГО ЦИЛИНДРА - Гетьман, А.В.; Константинов, А.В. (Інститут електродинаміки НАН України, Київ, 2012)
There was the applying of cylindrical harmonics analysis for analytical description of relic and inductively magnetisation, and also magnetic field of linear magnetised cylinder observed. One considers properties of representation for outer and inner magnetic field on basis of cylindrical harmonics for the case of homogeneously magnetised cylinder and the case of the cylinder, which magnetising is set as analytical function. The results in a case of homogeneously magnetized cylinder were received using two models of magnetisation: on a basis of fictive magnetic charge and on a basis of spatial distribution of magnetic dipoles. There is outer magnetic field of inductively magnetised cylinder, which could be represented similarly to the case of relic magnetisation a basis of the cylindrical harmonics. References 6.